The Matter of Relevance: notes on research, design, and making within practice - John Enright (Oz, 2009)
The spread of the word ‘design’ doesn’t come at a time when there is less to do; it comes at a time when there is more to do. Infinitely more, since it is the whole fabric of life that is now concerned thanks to the ecological crisis. What no revolution has contemplated, namely the remaking of our collective life on earth, is to be carried out with exactly the opposite of revolutionary and modernizing attitudes.